Scientific journals on disk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Livestock research for rural development is a scientific journal published entirely on computer diskette. It is now in its fourth volume and tenth issue and is received by over 1000 people worldwide. It was the result of cooperation between CIPAV...